Real-Time Navigation-Guided Drilling Technique for Skull Base Surgery in the Middle and Posterior Fossae - Ogiwara, Toshihiro (J Neurol Surg B Skull Base, 2018)
Objective  The usefulness of the bony surface registration method for navigation system image-guided surgery in the lateral or prone position has been reported. This study was performed to evaluate the efficacy of our new real-time navigation-guided drilling technique with bony surface registration for skull base surgery in the middle and posterior fossae. Methods  The study included 29 surgeries for skull base tumors that required drilling of the petrous bone between January 2015 and December 2017 in Shinshu University Hospital. A navigation system was used for drilling of the petrous bone as follows: (1) some labyrinthine structures were marked by color in the source image and superimposed on the navigation image on the workstation preoperatively; (2) bony surface registration was performed with a three-dimensional (3D) skull reconstruction model in the operating room; (3) the petrous bone was drilled under navigation guidance with real-time view-through confirmation of 3D color-marked labyrinthine structures with observation under a microscopic operative view. Results  Real-time identification of some structures in the petrous bone was performed, and adequate and precise drilling of the petrous bone was achieved without the risk of labyrinthine perforation or stress. Using this method, surgeons do not need to alternate their gaze between the surgical field and the navigation screen. Conclusions  Due to the development of bony surface registration, this new technique is useful for drilling petrous bone in the middle and posterior fossa skull base surgeries.